2013
DOI: 10.5505/phd.2013.07379
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Death Anxiety, Death Related Depression of Health Personnel Providing Emergency Medical Services and Their Coping Methods

Abstract: ÖZETAmaç: Bu çalışma, Düzce ilindeki acil tıp hizmeti veren sağlık personelinin ölüme ilişkin kaygı ve depresyon durumları ile kullandıkları başa çıkma yöntemlerini belirlemek amacıyla tanımlayıcı olarak yapılmıştır. Gereç ve Yöntem:Araştırmanın örneklemini Düzce ili sınırları içinde bulunan, acil tıp hizmeti veren kurumlarda çalışan 141 (78 kadın, 63 erkek) sağlık personeli oluşturmuştur. Araştırmanın verileri "Tanıtım Formu", "Templer'in Ölüm Kaygı Ölçeği" ve "Ölüme İlişkin Depresyon Ölçeği" uygulanarak topl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
1
6
0
4
Order By: Relevance
“…n our study, working at intensive care unit was considered as the factor increasing death anxiety. n Acehan s study, death anxiety was found to be higher in women 11 . Similarly, in studies conducted with other groups in the literature, death anxiety scores for women was found to be higher than that of men 16, 17 .…”
Section: Resultsmentioning
confidence: 83%
“…n our study, working at intensive care unit was considered as the factor increasing death anxiety. n Acehan s study, death anxiety was found to be higher in women 11 . Similarly, in studies conducted with other groups in the literature, death anxiety scores for women was found to be higher than that of men 16, 17 .…”
Section: Resultsmentioning
confidence: 83%
“…A study conducted by McKenzie and Brown (2017) revealed that death anxiety had direct negative effects on the capacity of the nurses to carry out their role effectively. In the literature, it is reported that factors such as age, gender, marital status, occupation, professional experience, witnessing death, beliefs, and coping strategies can affect people’s perception of death, meaning of death and life, attitudes and behaviors related to death, and the degree of death anxiety (Acehan & Eker, 2013; Ceyhan et al., 2018; McKenzie & Brown, 2017). In the study conducted by Acehan and Eker (2013) on the death anxiety of health-care staff who were working in the unit of emergency medicine, the score of the female health-care staff was higher ( p < .05) when compared with male health-care staff.…”
Section: Discussionmentioning
confidence: 99%
“…yapılan çalışmada da aynı sonuç bulunmuştur. 19 Bu sonuçlardan farklı olarak yaş arttıkça ölüm kaygısının azaldığını bildiren çalışmalar da mevcuttur. [20][21][22] Farklılığın, çalışma evreninin farklı olmasından kaynaklandığı düşünülmektedir.…”
Section: Bulgularunclassified
“…Konu ile ilgili yapılan farklı çalışmalar da benzer sonuçlar bildirilmiştir. 19,23 Çalışmada, çocuk sahibi olma ve ÖKÖ arasında anlamlı bir fark bulunmamıştır. Konu ile ilgili yapılan farklı bir çalışmada da benzer sonuç bildirilmiştir.…”
Section: Bulgularunclassified
See 1 more Smart Citation